2014
DOI: 10.1126/scitranslmed.3009885
|View full text |Cite
|
Sign up to set email alerts
|

Metformin as adjunct antituberculosis therapy

Abstract: Metformin can be repurposed as host-directed therapy for tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
531
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(584 citation statements)
references
References 51 publications
26
531
4
4
Order By: Relevance
“…Metformin (MetF), an AMP-activated protein kinase (AMPK)-activating drug for type 2 diabetes (DM), was reported to inhibit intracellular growth of mycobacteria by inducing reactive oxygen species and to enhance the efficacy of conventional anti-TB drugs in mouse models of acute and chronic TB; its use was associated with decreased TB severity and improved clinical outcomes in a retrospective analysis of 220 patients with DM and TB (6). In another retrospective study, Srujitha et al showed that MetF use was associated with a 3.9-fold reduction in TB incidence among patients with DM (7).…”
mentioning
confidence: 99%
“…Metformin (MetF), an AMP-activated protein kinase (AMPK)-activating drug for type 2 diabetes (DM), was reported to inhibit intracellular growth of mycobacteria by inducing reactive oxygen species and to enhance the efficacy of conventional anti-TB drugs in mouse models of acute and chronic TB; its use was associated with decreased TB severity and improved clinical outcomes in a retrospective analysis of 220 patients with DM and TB (6). In another retrospective study, Srujitha et al showed that MetF use was associated with a 3.9-fold reduction in TB incidence among patients with DM (7).…”
mentioning
confidence: 99%
“…132 AMPK is activated by metformin, a type-2 diabetes drug, 133 that reduces bacterial burden and ameliorates lung pathology in mice and humans by enhancing autophagy and increasing ROS production. 92 Metformin adjunctive treatment however failed to improve sterilizing activity and TB relapsed in mice, with no significant effect being reported for culture conversion rates in diabetes mellitus patients with TB. 134 …”
Section: Kinase Modulatorsmentioning
confidence: 99%
“…In addition, a DDI study in rats involving berberine and metformin interactions reported an increased initial plasma concentration and AUC for metformin, and a decreased systemic clearance and volume of distribution were observed for metformin due to the inhibition of OCT1 and OCT2 by berberine (33). Another study suggested the use of metformin as an adjunctive therapy to improve the efficacy of anti-TB drugs (34), but the findings of the current in vitro study suggest that consideration is warranted before prescribing anti-TB drugs with metformin. Again, we must emphasize that the interactions of these anti-TB drugs with multidrug and toxin extrusion (MATE) transporters play a major role in the renal clearance of cations as does OCT2.…”
Section: Discussionmentioning
confidence: 99%